DEMANDA DE CRÉDITOS AGRÍCOLAS EN LA AGENCIA BANECUADOR VINCES - CARPIO LOOR, ANGEL CARLOS (2018)
The present case study was developed taking into consideration the needs of agricultural producers in the canton of Vinces, by means of a preliminary diagnosis determined that the lack of financial resources for the acquisition of agricultural inputs, machinery, seeds for their activities is frequent, because the producers of the agricultural sector are people with little knowledge of the financial area, in addition to little knowledge about correct management and performance of their activities productive The lack of monetary resources of the agricultural sector is unfavorable, since not having the necessary resources, their activities and production are they paralyze, thus increasing the economic instability of the sector itself.